Think deeply about the future - Abd Razak, Dzulkifli (2009)
THINKING is no doubt an important activity! We often hear of complaints that "thinking" is missing in our classrooms and that it has been over taken by rote learning. Some research seem to claim that thinking in organisations is also not that common. Only two per cent are said to think, three per cent do not think; and the remaining 95 per cent think they think! This is not surprising given that thinking is actually hard work. It is allegedly equivalent to three hours of labourintensive work under the hot sun, according to some comparisons.